Nanoantibiotics: Functions and Properties at the Nanoscale to Combat Antibiotic Resistance - Mamun, M. Mustafa; Sorinolu, Adeola Julian; Munir, Mariya; Vejerano, Eric P. (Frontiers in Chemistry, 2021)
One primary mechanism for bacteria developing resistance is frequent exposure to antibiotics. Nanoantibiotics (nAbts) is one of the strategies being explored to counteract the surge of antibiotic resistant bacteria. nAbts are antibiotic molecules encapsulated with engineered nanoparticles (NPs) or artificially synthesized pure antibiotics with a size range of ≤100 nm in at least one dimension. NPs may restore drug efficacy because of their nanoscale functionalities. As carriers and delivery agents, nAbts can reach target sites inside a bacterium by crossing the cell membrane, interfering with cellular components, and damaging metabolic machinery. Nanoscale systems deliver antibiotics at enormous particle number concentrations. The unique size-, shape-, and composition-related properties of nAbts pose multiple simultaneous assaults on bacteria. Resistance of bacteria toward diverse nanoscale conjugates is considerably slower because NPs generate non-biological adverse effects. NPs physically break down bacteria and interfere with critical molecules used in bacterial processes. Genetic mutations from abiotic assault exerted by nAbts are less probable. This paper discusses how to exploit the fundamental physical and chemical properties of NPs to restore the efficacy of conventional antibiotics. We first described the concept of nAbts and explained their importance. We then summarized the critical physicochemical properties of nAbts that can be utilized in manufacturing and designing various nAbts types. nAbts epitomize a potential Trojan horse strategy to circumvent antibiotic resistance mechanisms. The availability of diverse types and multiple targets of nAbts is increasing due to advances in nanotechnology. Studying nanoscale functions and properties may provide an understanding in preventing future outbreaks caused by antibiotic resistance and in developing successful nAbts.